Femtosecond laser–assisted cataract surgery in eyes with shallow anterior chamber depth: comparison with conventional phacoemulsification. Issue 12 (December 2020) - Mencucci, Rita; De Vitto, Chiara; Cennamo, Michela; Vignapiano, Roberto; Buzzi, Matilde; Favuzza, Eleonora
Abstract : In eyes with shallow ACs, FLACS was a safe and an effective technique, reducing the postoperative endothelial cell loss and corneal inflammation compared with conventional phacoemulsification. Abstract : Purpose: To compare the postoperative outcomes between femtosecond laser–assisted cataract surgery (FLACS) and conventional phacoemulsification in eyes with shallow anterior chamber depth (ACD). Setting: Eye Clinic, NEUROFARBA Department, University of Florence, Italy. Design: Prospective case series. Methods: Forty eyes of 40 patients with senile cataract and true ACD less than 2.00 mm underwent FLACS (femto group, n = 20) or manual phacoemulsification (phacoemulsification group, n = 20). Preoperatively and 1 week and 1 month and 6 months postoperatively, central corneal thickness (CCT) and endothelial cell density were evaluated; basal epithelial cell (BEC) and Langerhans dendritic cell (LDC) densities and keratocyte activation were assessed using in vivo corneal confocal microscopy. Intraoperative parameters such as cumulative dissipated energy (CDE) and ultrasound (US) power were recorded. Results: Endothelial cell loss (ECL) was significantly lower in the femto group at all timepoints ( P ≤ .001). In the phacoemulsification group, the CCT was significantly higher 1 week ( P < .001) and 1 month ( P < .001) postoperatively than preoperatively; conversely, in the femto group, it was higher only after 1 week ( P < .001). BECs and LDCs significantly increased at 1 postoperative week ( P < .001), returning to preoperative values after 1 month in both groups. Keratocyte activation remained significantly higher at 1 postoperative month only in the phacoemulsification group ( P = .005). CDE and US power were lower in the femto group ( P = .017 and P = .001, respectively); they were correlated with ECL ( r = 0.662, P = .000; r = 0.389, P = .013). Conclusions: In eyes with shallow ACD, FLACS was a safe and an effective technique, significantly reducing the postoperative ECL and corneal inflammation compared with conventional phacoemulsification.